Site searching: To note and visualize unnoticed layers of a site - Frick, Catrin; Löfblad, Emma (My University, 2021)
To investigate the site is for most architects the first move when starting a new project. To thoroughly understand a place is fundamental for the design process. The design often relates to physical limitations on site but more seldom, it reflects the soft and unseen values and conditions that make out the narratives of the site. By exposing a place’s narratives one can begin to understand the historical and current function of it. We argued that those values are important to support the design. We want different layers of a place to distinguish throughout a site study. Therefore, this thesis aims to translate the conditions of a site into visual material that can be used to inform architectural design. The conditions of the site are extracted through the method of mapping by usage of notations and collages. The images created, in turn, work as new foundations for searching new knowledge of the site. We call it Site Searching. In today’s image saturated society, it is important to be critical and to decode the values and ideas that are embedded in the images we are being exposed to. We are influenced by images daily and what we see impacts our emotions and actions. This thesis works with visual literacy to challenge the way we communicate using images and to analyse our material. It aims to find out what conclusions can be made from the visual material we produce based on the investigations made on site. The examination takes place at Skanstorget in Gothenburg, a place that provides the opportunity to explore both past, present and future development. The site is well debated but still it awaits transformation. The current status quo of the site triggers an interest to uncover its layers. This thesis results in an archive that hosts some of the findings excavated during the process, displaying them as design informants. They are put to test in various design studies that question the potential of these designs affecting the site. The design studies are not supposed to supply answers, instead they further question the potential of design embodying layers of the site.
Keywords: Site exploration, narrative, archive, representation, design studies